Observer-based finite-region dissipative control of 2D FM systems. (19th July 2019) - Li, Lingling; Yang, Rongni
This paper is concerned with the problem of finite-region dissipative observer-based control for a class of discrete-time two-dimensional (2D) systems formulated by the Fornasini-Marchesini (FM) model subject to missing measurements. Firstly, the concepts of finite-region boundedness (FRB) and finite-region (T, S, R)-ϑ-dissipativity for 2D systems are introduced, respectively. Secondly, the FRB and finite-region (T, S, R)-ϑ-dissipativity are investigated for the resulting closed-loop systems, and then the corresponding conditions are derived. Based on the obtained results, the observer-based output feedback controller is designed, and the example of metal rolling process is employed to illustrate the effectiveness of the proposed design method.